Biologics and cardiac disease: challenges and opportunities. (November 2022) - Ciucci, Giulio; Colliva, Andrea; Vuerich, Roman; Pompilio, Giulio; Zacchigna, Serena
Abstract : Biologics are revolutionizing the treatment of chronic diseases, such as cancer and monogenic disorders, by overcoming the limits of classic therapeutic approaches using small molecules. However, the clinical use of biologics is limited for cardiovascular diseases (CVDs), which are the primary cause of morbidity and mortality worldwide. Here, we review the state-of-the-art use of biologics for cardiac disorders and provide a framework for understanding why they still struggle to enter the field. Some limitations are common and intrinsic to all biological drugs, whereas others depend on the complexity of cardiac disease. In our opinion, delineating these struggles will be valuable in developing and accelerating the approval of a new generation of biologics for CVDs. Highlights: Cardiovascular diseases represent the leading cause of death globally. However, biological drugs, which stand to be real gamechangers in other medical sectors such as cancer and immune and genetic diseases, struggle to enter the cardiovascular field. Biological drugs, or biologics, are medicinal products that are produced from living organisms and include recombinant proteins, gene therapy, and cell therapies. Their manufacture is far more complex than small-molecule drugs. Specific features of cardiac diseases may represent a challenge for the successful application of biologics in clinical settings. Overcoming these challenges may offer unprecedented opportunities to radically change the toolbox of drugs to treat cardiac diseases, with obvious societal and economic implications.